Insights into the structure–function relationship of both wild and mutant zinc transporter ZnT8 in human: a computational structural biology approach. Issue 1 (2nd January 2020) - Gupta, Manoj Kumar; Vadde, Ramakrishna
Abstract: Polymorphism rs13266634 in SLC30A8 causes abnormal synthesis, maturation and secretion of insulin, resulting in decrease in efficiency of glucose metabolism and diabetes. SLC30A8 encodes Zinc transporter 8 protein (ZnT8). Due to lack of NMR/crystal structures of complete ZnT8 transporter, insights into the structure, function and its interaction with different drugs is still not known. Therefore, in-silico methods were adopted in the present studies for predicting three-dimensional structure of ZnT8 transporter via comparative modelling approach and studying the impact of mutation (p.ARG325TRP) on architecture and function via simulation studies. Wild-type protein comprises 15 α-helix and 3 β-strands, while mutant consists of 12 α-helix and 2 β-strands, respectively. Interaction studies of mutant ZnT8 transporter with phytochemicals/drugs screened the best phytochemicals, which can retain the wild-type property. Molecular docking studies reveal that mutant proteins have better binding energy with ligands of LY-2608204, Roseoside, and Luzonoid B. Further molecular dynamic simulation analysis exhibited a strong binding of these ligands with mutant protein and displaying similar behaviour as that of wild type. ALA79, ILE80, and ARG215 are the common interacting amino acids with ligand in all three complexes. As the ligands passed ADMET tests, these may be utilized as anti-diabetic drugs in near future. Although earlier studies have reported anti-diabetic property of LY-2608204 and Roseoside, for the first time, this study reporting Luzonoid B may have anti-diabetic property besides elucidating the structure and functions of ZnT8 transporter.